The Influence of Perceived Parenting Style on Role Congruity and Emotional Intelligence - Knutson, Kris; Miller, Caitlin (My University, 2017)
Emotional Intelligence (EI) is the ability of an individual to recognize emotions in themselves and others, verbally and non-verbally express a wide variety of emotions, regulate emotional expression, and display emotions in a variety of ways (Schutteet al., 1997). Considering all this, the current study predicts: Males will report lower levels of EC parenting than females. Parenting style will mediate role congruity insomuch that (a) ED parenting will lead to higher role congruity for males and (b) lower role congruity for females, and that (c) EC parenting will lead to lower role congruity for males and (d) higher role congruity for females. Additionally, this study seeks to answer the following research question: does perceived parenting style have a relationship with participants’ self-reported EI?
Color poster with text, tables, and charts.
Keywords: Parenting; Gender roles; Emotional intelligence; Posters